2018
DOI: 10.1016/j.ijfoodmicro.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages reduce Yersinia enterocolitica contamination of food and kitchenware

Abstract: Yersinia enterocolitica, the primary cause of yersiniosis, is one of the most important foodborne pathogens globally and is associated with the consumption of raw contaminated pork. In the current study, four virulent bacteriophages (phages), one of Podoviridae (fHe-Yen3-01) and three of Myoviridae (fHe-Yen9-01, fHe-Yen9-02, and fHe-Yen9-03), capable of infecting Y. enterocolitica were isolated and characterized. fHe-Yen9-01 had the broadest host range (61.3% of strains, 65/106). It demonstrated a latent perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 59 publications
(53 reference statements)
0
33
0
1
Order By: Relevance
“…More recently, Jun et al [36] reported the isolation of three additional Myoviruses (fHe-Yen9-01, fHe-Yen9-02, and fHe-Yen9-03) from sewage in Finland capable of infecting Y. enterocolitica. Among these, phage fHe-Yen9-01 was characterized as it had the broadest host range lysing 65 of 106 (61.3%) of Yersinia strains tested and formed plaques on 53/81 (65.4%) of the Y. enterocolitica strains tested, including epidemiologically significant strains of serotype O:3, O:5,27, and O:9.…”
Section: Myovirusesmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Jun et al [36] reported the isolation of three additional Myoviruses (fHe-Yen9-01, fHe-Yen9-02, and fHe-Yen9-03) from sewage in Finland capable of infecting Y. enterocolitica. Among these, phage fHe-Yen9-01 was characterized as it had the broadest host range lysing 65 of 106 (61.3%) of Yersinia strains tested and formed plaques on 53/81 (65.4%) of the Y. enterocolitica strains tested, including epidemiologically significant strains of serotype O:3, O:5,27, and O:9.…”
Section: Myovirusesmentioning
confidence: 99%
“…Among these, phage fHe-Yen9-01 was characterized as it had the broadest host range lysing 65 of 106 (61.3%) of Yersinia strains tested and formed plaques on 53/81 (65.4%) of the Y. enterocolitica strains tested, including epidemiologically significant strains of serotype O:3, O:5,27, and O:9. The phage genome has a T4-like gene organization and is closely related to the aforementioned Yersinia phages ϕR1-RT and vB_YenM_TG1 [36]. In addition, fHe-Yen9-01 was shown to be stable across a pH range of 5-9 and did not contain genes related to lysogeny or associated with undesirable virulence factors that might preclude their use as biocontrol agents [36].…”
Section: Myovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the enterococcal phage Q69 was used in a cheese model by Ladero et al (), it resulted in a significantly lower accumulation of tyramine. In another study concerning the zoonotic pathogen Y. enterocolitica , phages were successfully applied to control this pathogen in artificially contaminated milk (Jun et al ). Phages have also been isolated against a variety of other dairy pathogens such as Brucella species, Bacillus subtilis and Campylobacter jejuni , and while no dairy applications have been published to date regarding these genera, the success of phages against the previously mentioned pathogens in dairy products is a good indicator of their potential for biocontrol in dairy products (Parnas et al ; Janež and Loc‐Carrillo ; Krasowska et al ).…”
Section: Exploitation Of Phages In Pathogen Biocontrolmentioning
confidence: 99%